Emerging Technologies and Circuits - Amara, Amara.; Ea, Thomas.; Belleville, Marc. (Lecture Notes in Electrical Engineering,, 2010)
With the semiconductor market growth, new Integrated Circuit designs are pushing the limit of the technology and in some cases, require specific fine-tuning of certain process modules in manufacturing. Thus the communities of design and technology are increasingly intertwined. The issues that require close interactions and collaboration for trade-off and optimization across the design/device/process fields are addressed in Emerging Technologies and Circuits. It contains a set of outstanding papers, keynote and tutorials presented during 3 days at the International Conference On Integrated Circuit Design and Technology (ICICDT) held in June 2008 in Minatec, Grenoble. The selected papers are spread over 5 chapters covering various aspects of emerging technologies and devices, advanced circuit design, reliability, variability issues and solutions, advanced memories and analog and mixed signals. All these papers are focusing on design and technology interactions and comply with the scope of the conference.